If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + y) = 3x + 2y (x * 5 + y * 5) = 3x + 2y (5x + 5y) = 3x + 2y Solving 5x + 5y = 3x + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5x + -3x + 5y = 3x + -3x + 2y Combine like terms: 5x + -3x = 2x 2x + 5y = 3x + -3x + 2y Combine like terms: 3x + -3x = 0 2x + 5y = 0 + 2y 2x + 5y = 2y Add '-5y' to each side of the equation. 2x + 5y + -5y = 2y + -5y Combine like terms: 5y + -5y = 0 2x + 0 = 2y + -5y 2x = 2y + -5y Combine like terms: 2y + -5y = -3y 2x = -3y Divide each side by '2'. x = -1.5y Simplifying x = -1.5y
| -15.4-3.5t=-(9.5t+0.4) | | -(6x-5y+4)= | | 5.1p-0.7(2+3p)=-10.4 | | 3/4y-6=1/4y+10 | | 28--4d=5d-17 | | 4+2(x-3)=20 | | 6x+6+2(9x-4)= | | 2b-3-10b-9= | | i(-i)= | | 0.25(8+4x)-0.5(10+2x)= | | 9w+w+8w= | | 3(x-1)+2(4x-5)=(x-3)+5 | | -2(7z+5)=-14z+13 | | 2sin^2x+3sinx+1=0 | | 3n^2-9n-3=0 | | -6w+19=8w+5 | | y+0.6y-1.2=2(y-1.4) | | -12x-14=-2(6x+7) | | h=-1+3l^2+s | | In(x-5)+In(x+6)=1 | | m^2+2mn-3n^2=0 | | X-3y=600 | | x^2+16x+64y^2=0 | | 5c+56=120 | | 9x+10=199 | | 128=3.14(8)(8)h | | 128=3.14(8)squaredh | | 3n+6-6=57-6 | | 44=w(2w-3) | | s=-.5gt+vt | | k^2-4k-24=0 | | Y=(9+4k)x |